Colonoscopic allergen provocation (COLAP): a new diagnostic approach for gastrointestinal food allergy. Issue 6 (June 1997) - Bischoff, S C; Mayer, J; Wedemeyer, J; Meier, P N; Zeck-Kapp, G; Wedi, B; Kapp, A; Cetin, Y; Gebel, M; Manns, M P
Abstract : BACKGROUND: The clinical relevance of gastrointestinal food allergy in adults is largely unknown because the mechanisms are poorly understood and the diagnosis is difficult to confirm. AIMS: To improve the diagnostic means for confirming intestinal food allergy on an objective basis, a new colonoscopic allergen provocation (COLAP) test was developed. PATIENTS: The COLAP test was performed in 70 adult patients with abdominal symptoms suspected to be related to food allergy, and in five healthy volunteers. METHODS: During the COLAP test, the caecal mucosa was challenged endoscopically with three food antigen extracts, a buffer control, and a positive control (histamine). The mucosal weal and flare reaction was registered semiquantitatively 20 minutes after challenge, and tissue biopsy specimens were examined for mast cell and eosinophil activation. RESULTS: No severe systemic anaphylactic reactions were found in response to intestinal challenge. The COLAP test was positive to at least one food antigen in 54 of 70 patients (77%), whereas no reaction in response to antigen was found in healthy volunteers. Antigen induced weal and flare reactions were correlated with intestinal mast cell and eosinophil activation, as well as with patients' history of adverse reactions to food, but not with serum concentrations of total or specific IgE or skin test results. CONCLUSION: The COLAP test may be a useful diagnostic measure in patients with suspected intestinal food allergy and may provide a new tool for the study of underlying mechanisms.